A survey on knowledge production in financing early childhood education - Santos, Joedson Brito dos (2020)
This article is part of a post-doctoral internship study and aims to inventory the scientific production on the financing of early childhood education (EI), in Brazil, between 1989 to 2019, considering aspects that indicate the research trajectory and the main topics investigated. It is a bibliographic and documentary research that brought together theses, dissertations, books, book chapters and articles. Capes' Theses and Dissertations Bank, the SciELO Platform, Google Scholar, the Fineduca magazine and the Lattes curriculum of researchers from the Fineduca network were used as data source. It is concluded that studies on EI financing have increased from the context of transition from Fundef to Fundeb, mainly in the post Fundeb, but it is still incipient with only 8 thesis papers, which suggests that the research field needs to consolidate. The thematic axes with the highest number of publications were: EI financing policy and expansion of service; EI Financing and the public-private relationship anstudies on EI Financing and Fund Policies. It is hoped that the present study can contribute with an overview of the production on the theme, point out aspects little explored, assist the work of future researchers, as well as promote the strengthening of studies on the targeting of public resources for EI.